Increased habenular connectivity in opioid users is associated with an α5 subunit nicotinic receptor genetic variant. (31st August 2017) - Curtis, Kaylah; Viswanath, Humsini; Velasquez, Kenia M.; Molfese, David L.; Harding, Mark J.; Aramayo, Eduardo; Baldwin, Philip R.; Ambrosi, Elisa; Madan, Alok; Patriquin, Michelle; Frueh, B. Christopher; Fowler, J.Christopher; et al.
Abstract : Background and Objectives: Opioid use disorder (OUD) is a chronic disorder with relapse based on both desire for reinforcement (craving) and avoidance of withdrawal. The aversive aspect of dependence and relapse has been associated with a small brain structure called the habenula, which expresses large numbers of both opioid and nicotinic receptors. Additionally, opioid withdrawal symptoms can be induced in opioid‐treated rodents by blocking not only opioid, but also nicotinic receptors. This receptor co‐localization and cross‐induction of withdrawal therefore might lead to genetic variation in the nicotinic receptor influencing development of human opioid dependence through its impact on the aversive components of opioid dependence. Methods: We studied habenular resting state functional connectivity with related brain structures, specifically the striatum. We compared abstinent psychiatric patients who use opioids ( N = 51) to psychiatric patients who do not ( N = 254) to identify an endophenotype of opioid use that focused on withdrawal avoidance and aversion rather than the more commonly examined craving aspects of relapse. Results: We found that habenula–striatal connectivity was stronger in opioid‐using patients. Increased habenula–striatum connectivity was observed in opioid‐using patients with the low risk rs16969968 GG genotype, but not in patients carrying the high risk AG or AA genotypes. Conclusions: We propose that increased habenula–striatum functional connectivity may be modulated by the nicotinic receptor variant rs16969968 and may lead to increased opioid use. Scientific Significance: Our data uncovered a promising brain target for development of novel anti‐addiction therapies and may help the development of personalized therapies against opioid abuse. (Am J Addict 2017;26:751–759)